Anti-spasmodic assessment of hydroalcoholic extract and essential oil of aerial part of Pycnocycla caespitosa Boiss. & Hausskn on rat ileum contractions - Hassan Sadraei; Gholamreza Asghari; Mahdi Alipour (Wolters Kluwer Medknow Publications, 2016)
Pycnocycla caespitosa is an essential oil-containing plant naturally growing in southwest of Iran. The extract of this plant has been used as remedy in traditional medicine. Another species of Pycnocyla (P. spinosa) possessed antispasmodic activity. The pharmacological objective of this study was to look for relaxant effect of hydroalcoholic extract and essential oil of P. caespitosa on rat isolated ileum contractions for comparison with loperamide. The essential oil and the hydroalcoholic extract were prepared by hydrodistillation and percolation techniques, respectively. For antispasmodic studies a section of rat ileum was suspended in an organ bath containing Tyrode's solution. The tissue was stimulated with electrical field stimulation (EFS), KCl (80 mM) and acetylcholine (ACh 0.5 μM). The tissue was kept under 1 g tension at 37 °C and continuously gassed with O 2 . The essential oil content in the aerial parts of P. caespitosa was found to be 0.16 % ml/g. The essential oil was analyzed by gas chromatography and gas chromatography-mass spectrometry. Seventy constituents, representing 97 % of the oil were identified. The major components of the oil were carvacrol (7.1%), β-eudesmol (6.4 %), ρ-cymene (5.7%), caryophyllene oxide (3.6%), α-pinine (1.4%) and α-phelandrene (1.1%). The hydroalcoholic extract of P. caespitosa inhibited the response to KCl (IC 50 = 48 ± 3 μg/ml), ACh (IC 50 = 61 ± 14.7 μg/ml) and EFS (IC 50 = 77 ± 17 μg/ml) in a concentration-dependent manner. The essential oil of P. caespitosa also inhibited rat ileum contractions. The IC 50 values for KCl, ACh and EFS were 9.2 ± 1.2 μg/ml, 7.6 ± 0.8 μg/ml and 6.4 ± 0.8 μg/ml, respectively. The inhibitory effect of both the essential oil and the extract were reversible. This research confirms the anti-spasmodic activity of both the essential oil and the extract of P. caespitosa on smooth muscle contraction of ileum.